2008
DOI: 10.1177/008124630803800410
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behaviour as Predictor of Entrepreneurial Intent Amongst Final-Year University Students

Abstract: The theory of planned behaviour (TPB) was tested as a predictor of entrepreneurial intent amongst final-year commerce students at two universities in the Western Cape (n = 247). The theoretical sufficiency of the theory was examined by considering four additional factors that are believed to influence entrepreneurial intention (i.e. personality traits, situational factors, prior exposure to entrepreneurship, and demographics). The results of the multivariate data analysis indicate that the TPB significantly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
151
5
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 39 publications
22
151
5
4
Order By: Relevance
“…First, by area of residence, graduates residing in the Seoul area were found to have greater propensity for startup intentions compared to those residing in all other regions except the Gyeongbuk and Gyeongnam provinces. As mentioned in previous studies, which state that diverse opportunities and education may influence startup intentions, this finding may be the result of the fact that Seoul offers a relatively wider range of opportunities to experience [8] [9]. Second, we found that parents" income level and level of education affected startup intentions.…”
Section: Conclusion and Suggestionssupporting
confidence: 66%
“…First, by area of residence, graduates residing in the Seoul area were found to have greater propensity for startup intentions compared to those residing in all other regions except the Gyeongbuk and Gyeongnam provinces. As mentioned in previous studies, which state that diverse opportunities and education may influence startup intentions, this finding may be the result of the fact that Seoul offers a relatively wider range of opportunities to experience [8] [9]. Second, we found that parents" income level and level of education affected startup intentions.…”
Section: Conclusion and Suggestionssupporting
confidence: 66%
“…Some examples of the implication of this theory are students' entrepreneurial intention in Turkey [3,20] also conducted a comparative study used this theory, [21] conducted another study in Africa. On the other hand, the list of examples of social entrepreneurial research on students include [22,23] in Egypt, and [24] in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To check the addition of the value to another variable hierarchical regression was done as used by [21] for checking their proposed hypothesis for the research on students' entrepreneurial intentions. Hierarchical regression allows researchers to check variables based on the theory for the proposed model [33].…”
Section: Russian University Students Intentions Towards Social Entrepmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPB integrates two lines of research on entrepreneurial intentions: research on the relationships between attitudes and entrepreneurial intention (Douglas & Shepherd, 2002), and research on the connections between self-efficacy and entrepreneurial intention (Jung, Ehrlich, DeNoble & Baik, 2001). The TPB has been used successfully in the past to describe entrepreneurial intentions of students in the U.S. (Autio, et al, 2001;Krueger, et al, 2000), The Netherlands (van Gelderen, et al, 2008), Norway (Kolvereid, 1996), Russia (Tkachev & Kolvereid, 1999), Finland, Sweden (Autio, et al, 2001), Germany (Jacob & Richter, 2005), Spain and Taiwan (Liñán & Chen, 2009;Moriano, 2005), and South Africa (Gird & Bagraim, 2008).…”
Section: Introductionmentioning
confidence: 99%